Biotransformation of arsenic by bacterial strains mediated by oxido-reductase enzyme system - Vishnoi, N.; Singh, D. P. (Cellular and Molecular Biology, 2014)
The present study deals with the enzyme mediated biotransformation of arsenic in five arsenic tolerant strains (Bacillus subtilis, Bacillus megaterium, Bacillus pumilus, Paenibacillus macerans and Escherichia coli). Biotransformation ability of these isolates was evaluated by monitoring arsenite oxidase and arsenate reductase activity. Results showed that arsenic oxidase activity was exclusively present in P. macerans and B. pumilus while B. subtilis, B. megaterium and E. coli strains showed presence of Arsenic oxido-reductase enzyme. The reversible nature of arsenic oxido- reductase suggested that same enzyme can carry out oxidation and reduction of arsenic depending upon the relative concentration of arsenic species. Lineweaver-Burk plot of the arsenite oxidase activity in P. macerans showed highest Km value (Km- 200 µM) and lower Vmax (0.012 µmol mg-1 protein min-1) indicating lowest affinity of the enzyme for arsenite. On the contrary, E. coli showed the lower Km value ( Km- 38.46 µM) and higher Vmax (0.044 µmol mg-1 protein min-1) suggesting for higher affinity for the arsenite. Lineweaver-Burk plot of arsenate reductase activity showed the presence of this enzyme in B. subtilis, B. megaterium and E. coli which were in the range of 200-360 µM Km and Vmax value between 0.256- 0.129 mmol mg-1 protein min-1. These results suggested that affinity of the as reductase enzyme is lowest for arsenate than that for the arsenite. Thus, arsenite oxidase system appears to be a predominant mechanism of cellular defense in these bacterial strains.